2022
DOI: 10.1021/acs.jpclett.2c00176
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Layer-Defined Asymmetric Schottky Contacts in Organic Planar Diodes for Self-Powered Optoelectronic Synapses

Abstract: Optoelectronic synapses have been utilized as neuromorphic vision sensors for image preprocessing in artificial visual systems. Self-powered optoelectronic synapses, which can directly convert optical power into electrical power, are promising for practical applications. The Schottky junction tends to be a promising candidate as the energy source for electrical operations. However, fully utilizing the potential of Schottky barriers is still challenging. Herein, organic self-powered optoelectronic synapses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…MoS 2 /pV3D3 Charge trapping [61] Image sharpening Multispectral sensing C 8 -BTBT/F 16 CuPc/PMMA Asymmetric heterojunctions Charge trapping [62] Pattern recognition CDs/silk Charge trapping [63] Facial recognition Organic-inorganic halide PQDs Charge trapping [64] Dynamic recognition P(VDF-TrFE)/Cs 2 AgBiBr 6 Charge trapping [65] a) Poly(d,l-lactic acid)-g-polyacrylic acid/polyethylene glycol. b) Poly{2,2-[(2,5-bis(2-hexyldecyl)-3,6-dioxo-2,3,5,6-tetrahydropyrrolo [3,4-c]pyrrole-1,4-diyl)dithiophene]-5,5′-diylalt-thiophen-2,5-diyl}: [6,6]-phenyl-C61-butyric acid methyl ester.…”
Section: Image Denoising Contrast Enhancementmentioning
confidence: 99%
See 3 more Smart Citations
“…MoS 2 /pV3D3 Charge trapping [61] Image sharpening Multispectral sensing C 8 -BTBT/F 16 CuPc/PMMA Asymmetric heterojunctions Charge trapping [62] Pattern recognition CDs/silk Charge trapping [63] Facial recognition Organic-inorganic halide PQDs Charge trapping [64] Dynamic recognition P(VDF-TrFE)/Cs 2 AgBiBr 6 Charge trapping [65] a) Poly(d,l-lactic acid)-g-polyacrylic acid/polyethylene glycol. b) Poly{2,2-[(2,5-bis(2-hexyldecyl)-3,6-dioxo-2,3,5,6-tetrahydropyrrolo [3,4-c]pyrrole-1,4-diyl)dithiophene]-5,5′-diylalt-thiophen-2,5-diyl}: [6,6]-phenyl-C61-butyric acid methyl ester.…”
Section: Image Denoising Contrast Enhancementmentioning
confidence: 99%
“…In addition, in order to further imitate the intelligent processing of the retina, it is important to fabricate self-powered artificial optoelectronic synapses through appropriate material and device structure design. [61,62,77] Hao et al demonstrated that a self-powered artificial optoelectronic synapse based on organic asymmetric heterostructures was able to perform image sharpening preprocessing with zero-powered synaptic plasticity (Figure 4b). [62] Semivertical organic asymmetric heterojunction devices based on dioctylbenzothienobenzothiophene (C 8 -BTBT) and hexadecafluorophthalocyanine (F 16 CuPc) exhibited typical photovoltaic responses.…”
Section: Neuromorphic Image Processing Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photo-excited electron-hole pairs can significantly impact the conductivity of devices by altering carrier concentration at the semiconductor and interface, which can in turn affect the contact barrier [115][116][117][118][119]. Among the mechanisms of the optical modulation barrier, the metal-semiconductor interface contact barrier is the most common.…”
Section: Metal-semiconductor Contact Barriermentioning
confidence: 99%